Plant cell biology : a practical approach - Hawes, C. R.; Satiat-Jeunemaitre, Béatrice (Oxford University Press, 2001)
The 'post genomics' era has seen a surge in demand for the techniques of cell biology, to aid in interpreting the function and location of the cell's myriad proteins and macromolecules. This new edition of Plant Cell Biology provides a grounding in established procedures before guiding the reader through the field's most current techniques. It provides advanced undergraduates, postgraduates and research staff in the plant sciences with a uniquelycomprehensive guide to this rapidly expanding discipline.
Keywords: Botanical microscopy -- Technique.; Plant cytochemistry -- Technique.; Plant cells and tissues.; Plantes -- Microscopie -- Technique.; Cytochimie végétale -- Technique.; Plantes -- Cellules et tissus.; SCIENCE -- Life Sciences -- Cell Biology.; Botanical microscopy -- Technique; Plant cells and tissues; Plant cytochemistry -- Technique; Planten.; Cytochemie.; Microscopie.